Molecular beam epitaxy of dilute nitride indium antimonide materials for long wavelength infrared application - Pham, Huynh Tram (2014)
InSb is an important material for high frequency electronic devices and for mid-infrared radiation detection. By adding a small amount of N into InSb, the band gap is found to decrease and this is useful for long wavelength infrared detector application. The main objectives of this thesis are to investigate the effect of N incorporation in InSbN and control the N incorporation to obtain the desired band gap. In addition, growth and doping of InSb material are also studied and optimized as they are necessary for the development of photon detector. The most advanced crystal growth technologies to date are utilized in the study: solid-source molecular beam epitaxy equipped with Sb valved cracker cell, CBr4 source, and N radio frequency (RF) plasma. The as-grown epitaxial layers are analyzed using chemical and physical characterization (x-ray diffraction, secondary ion mass spectrometry, xray photoelectron spectroscopy), electrical characterization (Hall effect measurement), and optical characterization (Raman spectroscopy, Fourier transform infrared spectroscopy, photocurrent measurement) techniques.